Exploring Attributes of Ethical Leadership and Ethical Guidelines in Malaysian Public Sector - Mohamed, Norazamina; Abdullah, Azizah; Marha Yaacob, Najihah; Ahmad, Suraya (International Journal of Engineering and Technology, 2018)
State departments, federal departments, statutory bodies, local authorities and district and land office of Malaysian Public Sector are responsible to provide ethical and efficient public services. However, due to the absence of ethical leadership and organizational ethical guidelines, cases of corruption and mismanagement continue to occur in the public sector. Thus, the objective of this paper is to explore the attributes of ethical leadership and ethical guidelines in Malaysian public sector. This study employs a qualitative research by analyzing data from interviews with key informers of public sector using conceptual content analysis. The study reveals role model, attachment, ethical support, knowledgeable, disciplined, shared values, virtue values and leaders’ spirituality encouragement as the attributes of ethical leadership. Meanwhile, guidance, communication, check and balance, concern on stakeholders and compliance are the attributes of ethical guidelines.   These identified attributes should become the ethical identity and ethical direction of Malaysian Public Sector. Thus, ethical leadership and ethical guidelines are to be the internal mechanism for organizational ethical self-identity precautionary. This would enhance the public trust as well as the international community trust towards public sector.